PELATIHAN PENYUSUNAN LAPORAN KEUANGAN PERUSAHAAN DAGANG KEPADA SISWA/I SMA SANTO KRISTOFORUS 1 JAKARTA BARAT - Virginia Patricia; Elsa Imelda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
With the rapid economic growth in Indonesia, the business world will also develop. The role of accountants in the present and future will be very important, therefore it is necessary to instill accounting knowledge from an early age, especially regarding procedures for preparing financial reports in trading companies. Upon an agreement with a school partner, the PKM team will provide accounting training regarding the procedures for preparing financial reports in trading companies at Santo Kristoforus 1 High School. This training was carried out offline 2 times. The first meeting took place on Friday, 13 October 2023 and the second meeting took place on Wednesday, 18 October 2023. The training participants involved students from Santo Kristoforus 1 High School grades 10 to 12. Training activities were delivered through theoretical discussions, discussion of practice questions, games session, and questionnaire session, with the aim of making students understand the material well. From the training activities that have been carried out, it can be concluded that the students of Santo Kristoforus 1 High School have understood the material regarding the preparation of financial reports in trading companies. This can be seen from the students' activeness in asking questions about the material during discussions, enthusiasm when working on practice questions, high spirits when playing in games session, and high average assessment results in the questionnaire session. Through this training, the PKM team hopes that Santo Kristoforus 1 High School students' interest in accounting lessons will increase, and can even inspire them to continue their education to college in the accounting study program.